Teaching Process and Emotional Reactions in Mathematics - Shiv Kant Tiwari; Dragan Obradovic; Laxmi Rathour; Lakshmi Narayan Mishra; Vishnu Narayan Mishra (The Journal of Engineering and Exact Sciences)
Teachers are increasingly required to have mathematical subject knowledge described as lists of facts, skills and competencies. Different emotional reactions are present in the classroom every day. Emotional reactions are most often divided into positive and negative, and negative emotional reactions are most often related to the evaluation process. Teaching mathematics at all stages and levels of education is often a challenge for students. It is known that mathematics is not very popular and one often hears this misconception: "common sense and mathematics do not go together". Unfortunately, statements such as "not for me", "I don't know math" and "my mom is not a mathematician" can often be heard from students. The popularity of mathematics is on the scale of less popular subjects in schools, although teachers are forcing the teaching of mathematics, and even the curriculum offers more math classes than some other subjects.